PLANT REGENERATION VIA ORGANOGENESIS FROM SIX FAMILIES OF LOBLOLLY PINE. - TANG, WI; FAN OUYANG
Organogenesis was induced in callus derived from mature zygotic embryos of six faniilies of loblolly pine (Pinus taeda L.) within 24 weeks of culture. Elongation of adventitious buds was achieved on TE medium supplemented with 0.5 mg 1-1 indole-3-butyric acid (IBA) and 2 mg 1-1 6-benzyladenine (BA). The most suitable inedium for root formation proved to be TE medium supplemented with 0. 1 mg 1-IBA, 1 mg 1- BA, and 0.5 mg 1- 1 gibberellic acid (GA3)- One hundred and sixty-nine regenerated plantlets were transferred to a perlite:peatmoss:vermiculite (1: 1: 1) soil mixture, and 98 plantlets survived in the field.
Keywords: ORGANOGENESIS; PINO; REGENERACION DE PLANTAS; PINUS TAEDA; CULTIVO IN VITRO; BIOTECNOLOGIA; Artículos de revista